Developing Physics Learning Media Based on Augmented Reality to Improve Students’ Critical Thinking Skills - Hannatun Nusroh; Muhammad Ardhi Khalif; Affa Ardhi Saputri (Faculty of Science and Education, UIN Walisongo Semarang, 2022)
Media has a significant role in achieving learning objectives, including critical thinking skills. This study develops Augmented Reality-based physics learning media to improve students’ critical thinking skills in XI class of senior high schools on optical instruments. This is Research and Development (RD) through the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The study was conducted with a small-scale trial of 30 students of XI class MIPA 1 MAN Demak. The instruments used were expert validation sheets, teacher and student response sheets, and pre-test and post-test questions for students’ critical thinking skills. The product feasibility test is carried out based on the validation results of media and material experts. N-gain test is used to determine the improvement of students’ critical thinking skills. The feasibility test results show that Augmented Reality-based learning media on optical instruments is feasible, with a feasibility score percentage of 78.79% (valid) based on media experts and 90% (very valid) based on material experts. The learning media received an excellent response from the physics teacher with an average score of 4.27 (very good) and 4.28 (very good) from the students. The use of physics learning media has increased students' critical thinking skills, based on the N-gain test results of 0.415 with moderate improvement criteria. Augmented Reality-based learning media can be applied to improve students' critical thinking skills.